2017
DOI: 10.1007/978-3-319-63318-3
|View full text |Cite
|
Sign up to set email alerts
|

Fallibility at Work

Abstract: adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made. The images or other third party material in this book are included in the book's Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the book's Creative Commons license and your intended use is not permitted by statutor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Unsurprisingly, when confronted with fallibility, managers often react defensively (Corlett et al, 2019), in ways such as those noted by Watson (2001: 178) where he "observed managers being rude to their staff, refusing to listen to advice given to them…curtly announcing unexplained decisions, losing their tempers with people… [and] creating rows with fellow managers". Crucially, this closes opportunities for learning (Kvalnes, 2017) since it can lead to "the avoidance of difficult questions, myopic thinking, repression of doubt, and the stifling of reflexivity" (Saggurthi & Thakur, 2016: 181), resulting in what Alvesson and Spicer (2015) term 'self-reinforcing stupidity' where no space is left for inquiry or improvement. Ironically, avoiding the transformative potential of fallibility's unsettling might mean that error and failure are more likely leading to grave social consequences.…”
Section: The Neglect Of Fallibility In Management Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, when confronted with fallibility, managers often react defensively (Corlett et al, 2019), in ways such as those noted by Watson (2001: 178) where he "observed managers being rude to their staff, refusing to listen to advice given to them…curtly announcing unexplained decisions, losing their tempers with people… [and] creating rows with fellow managers". Crucially, this closes opportunities for learning (Kvalnes, 2017) since it can lead to "the avoidance of difficult questions, myopic thinking, repression of doubt, and the stifling of reflexivity" (Saggurthi & Thakur, 2016: 181), resulting in what Alvesson and Spicer (2015) term 'self-reinforcing stupidity' where no space is left for inquiry or improvement. Ironically, avoiding the transformative potential of fallibility's unsettling might mean that error and failure are more likely leading to grave social consequences.…”
Section: The Neglect Of Fallibility In Management Learningmentioning
confidence: 99%
“…Managers then oftentimes do not know, are wrong, make mistakes and fail. Fallibility, simply defined by its Latin roots as being liable to error, (cf Kvalnes, 2017), that is, to outcomes which are experienced as negative and unexpected (Harrowell, Davies, & Disney, 2018), then constitutes a key aspect of managing (Deslandes, 2020). Yet since fallibility also involves a 'felt sense' or unsettling which reveals a vulnerability to harm (Segal, 2011), it is typically conceived as individual weakness, and as such, is routinely silenced.…”
Section: Introductionmentioning
confidence: 99%
“…Worst still, the requirement to deceive was seen by the owners as a feature of high-quality and professional customer service. As rightly noted by Kvalnes (2017), "Organizational life can place us at the top of slippery slopes, where the first small steps into dishonesty and cheating can lead to major moral deviances later" (p. 138). Therefore, this review provided evidence that corporate wrongdoing can take my forms, ways and be practiced by distinct companies.…”
Section: Other Organizational Dysfunctionalitiesmentioning
confidence: 99%
“…Social behavior might be an important factor that affects first aid willingness. Previous studies found that people hesitate to act in groups in an emergency due to the diffusion of responsibility [21,22]. Thus, investigating social behavior is the key to understanding more about first aid willingness.…”
Section: Introductionmentioning
confidence: 99%